Failed transcatheter mitral valve-in-ring implantation followed by transapical valve-in-valve within the ring and ad hoc paravalvular leak closure - Çakal, Beytullah; Çakal, Sinem; Güneş, Hacı Murat; Omaygenç, Mehmet Onur; Yıldırım, Aydın (Turkish Society of Cardiology, 2021)
There is a rapid emergence of transcatheter mitral valve-invalve (TMVIV) and valve-in-ring (TMVIR) techniques as an alternative to the conventional surgical valve replacement in ineligible patients requiring repeat surgery (1).The selection of a new transcatheter heart valve (THV) for degenerated surgical valves is relatively simple; however, the selection of valves for mitral rings is more nuanced because the rigidoval or D-shaped rings will not conform to the round shape of theprosthesis, thus posing a high risk of paravalvular leak (PVL).Although prior reports have described simultaneous TMVIVand percutaneous PVL closure techniques, our case report provides the first description of simultaneous transapical valve-invalve implantation and the closure of severe PVL after a failedtransseptal valve-in-ring procedure (2, 3).
Keywords: Hoc Paravalvular; Transcatheter Mitral; Implantation